2014
DOI: 10.1093/jnci/dju156
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Morbidity and Mortality After Treatment for Ductal Carcinoma In Situ of the Breast

Abstract: BackgroundRecent concerns about potential overdiagnosis and overtreatment of ductal carcinoma in situ of the breast (DCIS) render evaluation of late effects of treatment, such as cardiovascular disease (CVD), of great importance. We studied cardiovascular morbidity and mortality in a large population-based cohort of DCIS patients.MethodsData on all incident DCIS case patients in the Netherlands between 1989 and 2004 who were diagnosed before the age of 75 years were obtained (n = 10468). CVD data was acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…The critical point in survival care appears after the discharge from oncology or specialist care, when these women remain at long-term risk of complications due to treatment and the risk of relapses [13]. However, it is not clear whether women who have received cancer therapy are more likely to develop other comorbidities than those without a history of cancer [14]. Because of this, it is essential that breast cancer survivors, besides breast cancer specific prevention, receive the standardized preventive care as the women without cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…The critical point in survival care appears after the discharge from oncology or specialist care, when these women remain at long-term risk of complications due to treatment and the risk of relapses [13]. However, it is not clear whether women who have received cancer therapy are more likely to develop other comorbidities than those without a history of cancer [14]. Because of this, it is essential that breast cancer survivors, besides breast cancer specific prevention, receive the standardized preventive care as the women without cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…107,114,115 The reductions in mortality risk have been attributed to modern radiotherapy techniques, leading to reduction in dose delivery to the heart and coronary arteries. The transition to megavoltage radiotherapy systems has reduced the mean dose to the heart by approximately 50% (4.7-2.3 Gy), 116 while other contributors to dose reduction include breath-hold techniques, respiratory gating and prone positioning.…”
Section: 97mentioning
confidence: 99%
“…This should also include the fact that the risk of severe late adverse effects due to RT is low nowadays if RT is performed according to guideline recommendations [2,21,22]. A recent population-based study from the Netherlands found no increased risk for cardiovascular morbidity or mortality in patients with DCIS treated with postoperative RT [23]. …”
Section: Results Of Rt In Low-risk Dcis: the Rtog 9804 Trialmentioning
confidence: 99%